Association between COVID-19 mandatory lockdown and decreased incidence of preterm births and neonatal mortality - Cuestas, Eduardo (2021)
Previous studies suggest a decrease in preterm births (PTB) during de coronavirus disease 2019 (COVID-19), possibly due to the effect of the mandatory lockdown. Nevertheless, other reports have been unable to confirm this finding. Most of these studies originated in high-income countries and evaluated a limited number of potential confounders, and all of them assessed a short lockdown period. In addition, an important question remains unanswered: How can we be sure that the observed changes are due to lockdown, when most of the pregnancies delivered in the lockdown period were conceived prior to it?To date there is insufficient evidence to support the notion that public health interventions during the lockdown prevent PTB . The aim of this study was to compare the incidence of PTB, neonatal mortality (NM) and stillbirths adjusted by potential confounders during the lockdown period assessing a time window of nine and a half months during which all the pregnancies analyzed in the exposed group were conceived after the lockdown, with the corresponding incidence in the previous year where all the unexposed pregnancies analyzed were conceived before the lockdown.